Cross-Cultural Validation of the York Measure of Quality of Intensive Behavioral Intervention. (November 2017) - Långh, Ulrika; Cauvet, Elodie; Hammar, Martin; Bölte, Sven
Early intensive behavioral intervention (EIBI) is widely applied in young children with autism spectrum disorder. Little research has addressed the significance of adherence to EIBI practices for treatment outcomes. The York Measure of Quality of Intensive Behavioral Intervention (YMQI) was designed to assess EIBI quality delivery in Ontario, Canada. The objective of this study was to examine the cross-cultural validity of the YMQI in a clinical Swedish community sample of 30 boys and four girls with autism aged 2.5 to 6 years. Internal consistency was alpha = .87 for the full scale YMQI. Interrater reliability among three raters on 97 video-recorded therapy sequences was .71 (intraclass correlation coefficient [ICC]), and intrarater reliability of two raters re-scoring 15 sequences after 6 months was ICC = .87. The convergent validity of the YMQI with EIBI expert ratings was r = .49. Findings endorse the psychometric properties of the YMQI and its usability outside of Anglo-Saxon countries.